The Implementation of Analytical Hierarchy Process Method for Determining Livestock Alabio Duck Development Strategy in Rawa Hulu Sungai Utara - Yunandar, Yunandar; Effendi, Hefni; Widiatmaka, Widiatmaka; Setiawan, Yudi (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2021)
The cultivation of Alabio ducks (Anas Platyrynchos Borneo) so far is still natural and only involves one parameter; furthermore, each location has different characteristics. The hierarchical structure constructed has a ranking of importance as an alternative option for ducks' development in peatland ecosystems. This research aims to formulate a strategy for duck production in the Hulu Sungai Utara Regency. AHP (Analytical Hierarchy Process) method in this study is used to structure the decision-making flow from goals and alternatives and weigh the variables. Data collection was carried out with duck farming experts from academia, farmer groups, and policymakers. This study found that the availability of feed, both sago (0.254) and bran (0.218), is a significant component from an ecological perspective. Distance to market (0.307) and hatchery location (0.287) is an economic variable. The social part consists of distance from the settlement (0.443) and labor availability (0.247). Meanwhile, the availability of feed (0.282), hatchery technology (0.269), and Mina ducks (0.251) are the development strategies for duck cultivation in swamp areas, and economic stimulus (0.93) is the final contributor.